2001
DOI: 10.1172/jci10720
|View full text |Cite
|
Sign up to set email alerts
|

The discoidin domain receptor tyrosine kinase DDR1 in arterial wound repair

Abstract: IntroductionAtherosclerosis and restenosis are characterized by the development of a thickened neointimal layer in the blood vessel wall. Smooth muscle cells (SMCs) are activated after arterial injury and contribute to neointimal lesion development through proliferation, migration, and ECM synthesis. Recent research suggests that the ECM is not simply an inert scaffold, but instead there are dynamic interactions between cells and matrix that contribute to SMC responses. After arterial injury, SMCs synthesize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
171
2
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(182 citation statements)
references
References 31 publications
5
171
2
3
Order By: Relevance
“…4 -6 A number of studies have shown that DDR1 is implicated in carcinogenesis, inflammation, atherosclerosis, and fibrogenesis. [7][8][9][10][11][12] Consistent with an important pathogenetic role in vascular diseases, 8,[13][14][15] we have demonstrated that DDR1-deficient mice were protected against renal vascular lesions induced by a long-term infusion of angiotensin II, a model in which hemodynamic alterations and vascular remodeling play a major role. 11 Whether DDR1 may contribute to the initiating mechanisms and the progression of renal fibrosis irrespective of the initial cause remains unclear.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…4 -6 A number of studies have shown that DDR1 is implicated in carcinogenesis, inflammation, atherosclerosis, and fibrogenesis. [7][8][9][10][11][12] Consistent with an important pathogenetic role in vascular diseases, 8,[13][14][15] we have demonstrated that DDR1-deficient mice were protected against renal vascular lesions induced by a long-term infusion of angiotensin II, a model in which hemodynamic alterations and vascular remodeling play a major role. 11 Whether DDR1 may contribute to the initiating mechanisms and the progression of renal fibrosis irrespective of the initial cause remains unclear.…”
mentioning
confidence: 63%
“…The generation and genotyping of mice were described previously. 13,16 The original background of the DDR1-null mice was a mix of 129/Sv with CD1. These mice have been backcrossed seven times to 129/Sv.…”
Section: Transgenic Micementioning
confidence: 99%
“…Furthermore we have shown that DDR1 is an independent favourable prognostic marker for early-stage NSCLC patients, and that mutations in DDR1 and DDR2 appear less frequently than previously reported. The collagen-binding RTKs, DDR1 and DDR2, have previously been linked to various human diseases including fibrosis (Alves et al, 1995;Mao et al, 2002;Lee et al, 2004;Avivi-Green et al, 2006), atherosclerosis (Hou et al, 2001;Hou et al, 2002;Ferri et al, 2004), and cancer (Johnson et al, 1993;Alves et al, 1995;Barker et al, 1995;Nemoto et al, 1997;Weiner et al, 2000;Dejmek et al, 2003;Ongusaha et al, 2003;Heinzelmann-Schwarz et al, 2004;Ram et al, 2006;Vogel et al, 2006). The mechanism by which DDRs may contribute to oncogenesis is as yet unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Using DDR1-null mice, we determined that DDR1 played a critical role mediating neointimal hyperplasia after arterial injury. 25 Furthermore, Ddr1 -/-SMCs exhibited reduced proliferation, migration, and MMP activity in response to type I or type VIII collagen in vitro, 25 and overexpression of DDR1 rescued these deficits. 30 In agreement with this, overexpression of DDR1 or DDR2 in human SMCs increased MMP-1 expression and decreased procollagen α 1 (I) mRNA expression.…”
Section: Collagen Remodeling Smooth Muscle Cell Proliferation and MImentioning
confidence: 99%